ANALYSIS OF THE TRAVELLING FORKLIFT IN MATERIAL TRANSPORT ACTIVITIES IN A MANUFACTURING PLANT - N., Awang; A.Y., Bani Hashim; Z., Jamaludin, (Journal of Advanced Manufacturing Technology (JAMT), 2014)
Analysis of forklifts movement within actual manufacturing plant environment was performed. It was intended to study current efficiency in parts delivery using Arena simulation software. The work proposed improvements for the current manufacturing arrangement to achieve a greater efficiency. The results show that there was an improved efficiency at a distance of 100 meters based on the proposed layout. This improvement was indicated by the reduction in the non-added value from 3.0 seconds to 2.4 seconds. This analysis concludes that the proposed changes to the current material transport activities could improve the material transport efficiency at the manufacturing plant.